2022
DOI: 10.1007/s11356-022-24871-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on spatio-temporal variation and hydrological connectivity of tidal creek evolution in Yancheng coastal wetlands

Abstract: Tidal creek is an important natural carrier of hydrological connectivity in coastal wetlands, and an important channel for material exchange between sea and land. Based on the remote sensing image data from 1987 to 2020, the spatio-temporal divergence patterns of tidal creek network and its hydrological connectivity were revealed. The results showed that: (1) The morphology of tidal creeks was similar to the "tree-shaped" development, and the tidal creeks at all grades tended to be "short, fragmented and paral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Remote sensing satellite image data have been increasingly useful for studying the relationship between vegetation and tidal creeks, as well as for establishing morphological characteristic indices in the presence of hydrological connectivity [11]. Recent studies suggested that the tidal gullies and wetland vegetation are interrelated [12,13]. The relationship between tidal creeks and vegetation distribution pattern in the Yangtze River delta, Yancheng nature reserve, and Yellow River delta has been established by examining the drainage efficiency of vegetation-free and vegetation-covered tidal creek networks, the evolution of tidal creeks, and the expansion of Spartina alterniflora [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing satellite image data have been increasingly useful for studying the relationship between vegetation and tidal creeks, as well as for establishing morphological characteristic indices in the presence of hydrological connectivity [11]. Recent studies suggested that the tidal gullies and wetland vegetation are interrelated [12,13]. The relationship between tidal creeks and vegetation distribution pattern in the Yangtze River delta, Yancheng nature reserve, and Yellow River delta has been established by examining the drainage efficiency of vegetation-free and vegetation-covered tidal creek networks, the evolution of tidal creeks, and the expansion of Spartina alterniflora [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Indices and simple measures have been used to represent the degree of connectivity of tidal creeks in the presence of reclamation activities. Indices representing the connectivity of tidal creeks include structural indices based on α, β, and γ [31,32]. Reclamation activities have been summarized by using rough measures, such as the population density or the area of reclamation in a given region [13], in light of human activities [15].…”
Section: Introductionmentioning
confidence: 99%